التحول الطاقوي في الجزائر: واقع ورهانات - عبدات, عبد الوهاب; دعاس, خليل (جامعة الوادي - University of Eloued, 2021)
تهدف هذه الدراسة إلى بحث إشكالية التحول الطاقوي والمبررات التي تقف خلف التوجه العالمي نحو تعزيز مكانة الطاقات المتجددة، مع عرض لمعالم سياسة التحول الطاقوي في الجزائر، وبحث الجهود المبذولة من أجل تحقيق تحول طاقوي سلس في الجزائر من خلال استعراض مضامين برنامج الطاقات المتجددة (2011-2030) ومقاربة الرهانات المرفوعة في إطار هذا البرنامج مع ما تحقق ميدانيا. This study aims to examine the problem of energy transformation and the rationale behind the global trend towards enhancing the status of renewable energies, while also describing the parameters of the energy transformation policy in Algeria. We will also try to examine the efforts to achieve a smooth energy transformation in Algeria by reviewing the contents of the renewable energies programme (2011-2030) and approaching of the bets raised under this programme to what has been achieved on the ground.
Keywords: التحول الطاقوي، الطاقات المتجددة، الطاقة الشمسية، برنامج الطاقات المتجددة، الانتقال الطاقوي